Psychological Counselling for Workers to Prevent Emotional Distress and Depression in a Manpower Supply Company in Doha, Qatar - Biswas, Rabindranath (Digital Repository of Theses, 2025)
The development of visible light on the “Psychological Counselling for Workers to Prevent Emotional Distress and Depression in a Manpower Supply Company in Doha, Qatar”. The study investigates the role of psychological counseling as a preventive measure to mitigate emotional distress and depression among workers in a manpower supply company. The study shows that a lot of people are having mental problems because of things like not knowing if they will have a job, working long hours, and moving to a new culture. The study addresses the significant mental health challenges faced by workers in this sector, including prolonged separation from family, high workloads, and job insecurity. A descriptive research design was adopted, integrating both primary and secondary data to provide comprehensive insights. To do a thorough statistical analysis, the study established commercial statistical tools like Excel and SPSS. There were many different statistical approaches to take into account for this study; nevertheless, the ones that were chosen were mean, standard deviation, correlation, regression, and t-test, depending on the objectives and hypotheses of the research. The results showed the significant impact of emotional distress and depression on individual well-being and productivity. The study additionally examined how well psychological counseling methods adapted to the workers' needs helped with these mental health problems. The study concludes with the importance of prioritizing mental health care in the workplace to enhance overall productivity, reduce absenteeism, and lower turnover rates.